1995
DOI: 10.1074/jbc.270.22.13548
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α2β1 Is a Positive Regulator of Collagenase (MMP-1) and Collagen α1(I) Gene Expression

Abstract: A classical model for studying the effects of extracellular matrix is to culture cells inside a three-dimensional collagen gel. When surrounded by fibrillar collagen, many cell types decrease the production of type I collagen, and the expression of interstitial collagenase (matrix metalloproteinase-1; MMP-1) is simultaneously induced. To study the role of the collagen-binding integrins alpha 1 beta 1 and alpha 2 beta 1 in this process, we used three different osteogenic cell lines with distinct patterns of put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
205
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(217 citation statements)
references
References 36 publications
11
205
0
Order By: Relevance
“…a3b1 integrin was shown to participate in phagocytosis of extracellular matrix (Coopman et al, 1996). a2b1, a3b1, a4b1, and a5b1 integrin were found to be involved in the regulation of matrix metalloprotease expression (Larjava et al, 1993;Huhtala et al, 1995;Riikonen et al, 1995). In addition, activation of a6b1 integrin increased invasiveness of LOX human melanoma cells correlating with a 2 ± 3-fold elevation of extracellular matrix degradation and invadopodial activity (Nakahra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a3b1 integrin was shown to participate in phagocytosis of extracellular matrix (Coopman et al, 1996). a2b1, a3b1, a4b1, and a5b1 integrin were found to be involved in the regulation of matrix metalloprotease expression (Larjava et al, 1993;Huhtala et al, 1995;Riikonen et al, 1995). In addition, activation of a6b1 integrin increased invasiveness of LOX human melanoma cells correlating with a 2 ± 3-fold elevation of extracellular matrix degradation and invadopodial activity (Nakahra et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Third, integrins are necessary for basement membrane penetration, since RGD peptides interfering with ligand binding to certain integrins prevented this process in vitro (Gehlsen et al, 1988). And ®nally, integrins are involved in the regulation of protease expression and their localized activities, as demonstrated in tissue culture experiments (Huhtala et al, 1995;Riikonen et al, 1995;Brooks et al, 1996;Coopman et al, 1996;Nakahara et al, 1996). In vivo changes in the metastatic potential of tumor cells often correlated with changes of the integrin expression pattern.…”
Section: Introductionmentioning
confidence: 99%
“…It was initially observed that antibodies blocking α 5 β 1 integrin-mediated adhesion induced MMP expression in fibroblasts (Werb et al, 1989). Later studies revealed that integrin-mediated signals are general regulators of MMP expression, as α 2 β 1 integrin regulates MMP-1 expression (Riikonen et al, 1995;Dumin et al, 2001), antibodies to α 3 β 1 integrin-tetraspanin complexes induce MMP-2 expression (Sugiura and Berditchevski, 1999), and α M β 2 and α 3 β 1 integrin ligation stimulates MMP-9 expression (Wize et al, 1998;Larjava et al, 1993). The effects on MMP expression are very specific.…”
Section: Expression and Secretion Of Gelatinases And Other Mmpsmentioning
confidence: 99%
“…Our previous data had shown Col 1 expression was two fold higher and expression for MMP-1, MMP-2, TIMP-1, and TIMP-2 increased for cells grown on 156 μg/cm 2 denatured collagen 17 . In this same study with 156 μg/cm 2 , with native collagen, Col-1 expression decreased by half and MMP-2 transcript levels increased by 2.5 fold in cell responses to denatured versus native collagen substrates at 4 day time points [35].…”
Section: Discussionmentioning
confidence: 82%
“…Cells recognize collagen matrices through the integrin family of transmembrane proteins; specifically, α 2 β 1 and α 1 β 1 integrin receptors [17]. The β1 integrins and the α2β1 integrin in particular have been associated with fibroblast collagen binding pathways [18,19].…”
Section: Introductionmentioning
confidence: 99%